2020
DOI: 10.2340/00015555-3615
|View full text |Cite
|
Sign up to set email alerts
|

Contact Allergy in Western Sweden to Propolis of Four Different Origins

Abstract: Propolis, which is produced by honeybees and is used in “natural” products, can cause contact allergy. The composition of propolis varies between regions, but little is known about how this variation affects contact allergenicity. The aims of this study were to investigate the frequency of propolis contact allergy in western Sweden, and whether the frequency varies according to the origin of the propolis. Patch-testing was performed using propolis from China, Lithuania, North America, and Sweden in 722 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
6
0
3
Order By: Relevance
“…In the current study of patients with dermatitis from Denmark, Lithuania and Spain, the same 4 batches of propolis from different geographical regions were used, as in our previous study of patients with dermatitis from western Sweden. The results from Denmark and Lithuania are in line with this study (Table I) (10), where positive reactions to any type of propolis were recorded in 6.2% of tested patients, ranging from 2.2% to 3.6% among the 4 types of propolis. In the Swedish patients, the frequency of positive reactions to any type of propolis was significantly higher (p < 0.0001), than that of the Spanish patients.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study of patients with dermatitis from Denmark, Lithuania and Spain, the same 4 batches of propolis from different geographical regions were used, as in our previous study of patients with dermatitis from western Sweden. The results from Denmark and Lithuania are in line with this study (Table I) (10), where positive reactions to any type of propolis were recorded in 6.2% of tested patients, ranging from 2.2% to 3.6% among the 4 types of propolis. In the Swedish patients, the frequency of positive reactions to any type of propolis was significantly higher (p < 0.0001), than that of the Spanish patients.…”
Section: Discussionsupporting
confidence: 88%
“…This was mainly attributed to difference in uptake mechanisms and/or biodistribution in body tissues of nano-sized particles, controlled release of the loaded drug, in addition to the overall improvement in the oral bioavailability of the encapsulated drug thus allowing dose reduction [ 73 , 74 ]. Therefore, the optimal nanoliposomal formulation of CAPE might reduce any adverse effects associated with the exposure to the free drug such as the reported propolis- and CAPE-induced allergy [ 75 , 76 , 77 ]. It has been shown that the most important allergic molecules in propolis are caffeic acid esters (especially caffeic acid phenyl ester), cinnamic acids and their aromatic esters [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since 2016, increased import and decreased export of propolis to and from Germany, respectively, probably indicate increased propolis use and exposure, which most likely explains the upward trend of propolis sensitization. Nevertheless, one has to be aware that differences in propolis composition, even between poplar‐type propolis species, and heterogeneity of the propolis used in PT preparations as well as in propolis on the (cosmetics) market do exist and affect diagnostic accuracy in patch tested patients, as recently demonstrated in a Swedish study 10 . The compositional (chemical) heterogeneity of commercially available PT preparations year on year should be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, one has to be aware that differences in propolis composition, even between poplar-type propolis species, and heterogeneity of the propolis used in PT preparations as well as in propolis on the (cosmetics) market do exist and affect diagnostic accuracy in patch tested patients, as recently demonstrated in a Swedish study. 10 The compositional (chemical) heterogeneity of commercially available PT preparations year on year should be studied.…”
Section: Discussionmentioning
confidence: 99%